Analisis Permasalahan Anak Autisme Di PAUD Harsya Ceria - Alfina Alfina; Shinta Delfianti; Syfa Penara; Hijriati Hijriati (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Special education means learning that is specifically designed to meet the unique needs of children with physical disabilities. Special education is a learning program prepared to meet the unique needs of an individual child. Education is a human effort to develop and guide personality in accordance with the values of society or as an effort to help students to increase knowledge and useful behavior patterns. Children with special needs are children who experience limitations or obstacles, whether physically, mentally, intellectually, socially or emotionally, such as: children with autism, hearing impairment, blindness, mental impairment, hearing impairment, physical impairment, etc. Harsya Ceria is a school with segregation services, where there are several children with different special needs. In making observations, the researcher focused on one child with autism, therefore the researcher tried to research this with the aim of finding out the problems of autistic children. There is a Harya cheerful preschool. The problems of children with special needs are of course different and varied, one of which is autism. They have the right to receive education like children in general. The method used in this research uses descriptive qualitative methods. Researchers collected descriptive data through interviews and observations. The results of this research show that children with autism have a variety of behaviors, therefore autism really needs attention from its caregivers. Harsya Ceria Paud provides good attention and needs to children with autism.